Sudden Occurrence of Roth Spots and Retinal Hemorrhages following Endoscopic Adhesiolysis: An SD-OCT Evaluation. Issue 1 (January 2016) - Dell'Arti, Laura; Barteselli, Giulio; Pinna, Valentina; Invernizzi, Alessandro; Mapelli, Chiara; Viola, Francesco
Purpose: To document the occurrence of Roth spots and retinal hemorrhages by spectral-domain optical coherence tomography (SD-OCT) following endoscopic adhesiolysis for failed back surgery syndrome. Methods: Case report. Results: A 47-year-old patient noted progressive and bilateral visual loss immediately after epidural endoscopy and endoscopic adhesiolysis. Funduscopic examination showed multiple Roth spots and retinal hemorrhages at the posterior pole and the retinal midperiphery in both eyes. Spectral-domain optical coherence tomography demonstrated that Roth spots involved the inner retina, while dot hemorrhages involved the outer retina. Most retinal hemorrhages and Roth spots resolved over 6 weeks, with complete functional recovery in both eyes. However, SD-OCT revealed multiple areas of disruption of the outer retinal layers in the left eye. Conclusions: Roth spots and retinal hemorrhages can occur after endoscopic spinal surgery. Although hemorrhages resolve quickly over few weeks, SD-OCT can demonstrate that retinal damage might persist, especially in the outer retina. This finding may explain cases of incomplete recovery of visual function after complicated endoscopic adhesiolysis.